Mechanical and thermal properties of montmorillonite-reinforced polypropylene/rice husk hybrid nanocomposites - Majeed, Khaliq; Ahmed, Ashfaq; Abu Bakar, Muhammad Saifullah; Mahlia, Teuku Meurah Indra; Saba, Naheed; Hassan, Azman; Jawaid, Mohammad; Hussain, Murid; Iqbal, Javed; Ali, Zulfiqar (MDPI, 2019)
In recent years, there has been considerable interest in the use of natural fibers as potential reinforcing fillers in polymer composites despite their hydrophilicity, which limits their widespread commercial application. The present study explored the fabrication of nanocomposites by melt mixing, using an internal mixer followed by a compression molding technique, and incorporating rice husk (RH) as a renewable natural filler, montmorillonite (MMT) nanoclay as water-resistant reinforcing nanoparticles, and polypropylene-grafted maleic anhydride (PP-g-MAH) as a compatibilizing agent. To correlate the effect of MMT delamination and MMT/RH dispersion in the composites, the mechanical and thermal properties of the composites were studied. XRD analysis revealed delamination of MMT platelets due to an increase in their interlayer spacing, and SEM micrographs indicated improved dispersion of the filler(s) from the use of compatibilizers. The mechanical properties were improved by the incorporation of MMT into the PP/RH system and the reinforcing effect was remarkable as a result of the use of compatibilizing agent. Prolonged water exposure of the prepared samples decreased their tensile and flexural properties. Interestingly, the maximum decrease was observed for PP/RH composites and the minimum was for MMT-reinforced and PP-g-MAH-compatibilized PP/RH composites. DSC results revealed an increase in crystallinity with the addition of filler(s), while the melting and crystallization temperatures remained unaltered. TGA revealed that MMT addition and its delamination in the composite systems improved the thermal stability of the developed nanocomposites. Overall, we conclude that MMT nanoclay is an effective water-resistant reinforcing nanoparticle that enhances the durability, mechanical properties, and thermal stability of composites.